A Cross-cultural Adaptation of A Measure of Intergenerational Family Relations, for Use in Brazil. Issue 2 (3rd April 2023) - Braz, Ana Carolina; Leme, V. R. B.; Barham, E. J.; Squassoni, C. E.; Coimbra, S.; Pizzani, L.; Fontaine, A. M. G. V.
ABSTRACT: We carried out a cross-cultural adaptation of the Intergenerational Solidarity Index, for use in Brazil (ISI-BR) with a sample of 682 people between the ages of 18 and 85. We used EFA, CFA and reliability measures. ISI-BR is a 24-item instrument with five factors: Functional solidarity, Affectual solidarity, Normative solidarity – obligations; Normative solidarity – values, and Conflict. Cronbach's alpha for the full scale was .84 and the composite reliability of the subscales ranged between .69 and .93, suggesting that they have good to excellent precision. We discuss the implications of this instrument for research, professional practice and public policy development.